GEOSPATIAL DASHBOARD FOR PROBLEM REPORTER IN JAMBI PROVINCE - Prasaja, Ahmad Syukron; Syaiful Huda, Imam Arifa'illah (LPPM UNIVERSITAS BINA INSAN, 2023)
Community involvement in providing problem reports is essential to improving the quality of life in cities and villages. Jambi already has